(untitled) (Global Journal of Science Frontier Research, 2023)
The article highlights experiments the Military Space Academy staff named after are considered A.F. Mozhaisky with artificial Earth satellites made it possible to detect an additional gravitating sphere in near-Earth space and her rotation.